2002
DOI: 10.1007/s00213-002-1283-z
|View full text |Cite
|
Sign up to set email alerts
|

A role for the prefrontal cortex in stress- and cocaine-induced reinstatement of cocaine seeking in rats

Abstract: These results suggest that the PL and OFC regions form part of the circuitry mediating the effects of foot shock stress on reinstatement of drug seeking and that the PL region may be a common pathway for cue, drug and foot-shock stress-induced reinstatement of drug seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
298
6
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(324 citation statements)
references
References 30 publications
17
298
6
3
Order By: Relevance
“…This work has shown that the circuitry involved in mediating reinstatement induced by footshock overlaps substantially with that involved in mediating reinstatement induced by drug-associated cues and by drug priming (Shaham et al, 2003). Thus, regions such as the VTA, the PFC and the nucleus accumbens are all part of the circuitry involved in these different types of reinstatement (Bossert et al, 2006Capriles et al, 2003;Fuchs et al, 2005;McFarland et al, 2004;McFarland and Kalivas, 2001). Local infusion of a D1 receptor antagonist into the PFC blocked footshockinduced reinstatement suggesting that such reinstatement could result from enhanced dopaminergic activity in the PFC (Capriles et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This work has shown that the circuitry involved in mediating reinstatement induced by footshock overlaps substantially with that involved in mediating reinstatement induced by drug-associated cues and by drug priming (Shaham et al, 2003). Thus, regions such as the VTA, the PFC and the nucleus accumbens are all part of the circuitry involved in these different types of reinstatement (Bossert et al, 2006Capriles et al, 2003;Fuchs et al, 2005;McFarland et al, 2004;McFarland and Kalivas, 2001). Local infusion of a D1 receptor antagonist into the PFC blocked footshockinduced reinstatement suggesting that such reinstatement could result from enhanced dopaminergic activity in the PFC (Capriles et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, regions such as the VTA, the PFC and the nucleus accumbens are all part of the circuitry involved in these different types of reinstatement (Bossert et al, 2006Capriles et al, 2003;Fuchs et al, 2005;McFarland et al, 2004;McFarland and Kalivas, 2001). Local infusion of a D1 receptor antagonist into the PFC blocked footshockinduced reinstatement suggesting that such reinstatement could result from enhanced dopaminergic activity in the PFC (Capriles et al, 2003). Yohimbine activates a number of brain regions that are also activated by footshock, including the nucleus accumbens, the VTA and the PFC (Funk et al, 2006;Singewald et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, physical stress (foot shock) given for various periods of time reinstated rat leverpressing for ethanol (Liu and Weiss 2003;Martin-Fardon et al 2000), cocaine (Capriles et al 2003;Lu et al 2001), heroin (Leri et al 2004;Shaham and Stewart 1996;Zhou et al 2008), and morphine (Mueller et al 2002). Also, immobilization stress given within the place preference chamber is capable of producing reinstatement of cocaine-seeking behavior in male Sprague-Dawley rats (Sanchez et al 2003).…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behmentioning
confidence: 99%
“…Imaging studies of cocaine addicts show that both cocaine and cocaine-paired cues increase metabolic activity in this circuit (Maas et al, 1998;Kilts et al, 2001;Grant et al, 1996;Breiter et al, 1997;Childress et al, 1999). Preclinical studies based on reinstatement models also point to the important role of this circuit in cocaine-seeking behavior (McFarland and Kalivas, 2001;Capriles et al, 2003;McLaughlin and See, 2003). In fact, preclinical evidence has identified specific receptor mechanisms by which various components of the mesocorticolimbic circuit control behavioral responses to cocaine.…”
Section: Introductionmentioning
confidence: 99%